The Role of Drug Ingestion Supervisors (DRUG SWALLOWING SUPERVISOR) Againstsuccess of Treatment of Pulmonary Tuberculosis in Puskesmas Surabaya - Ima Nadatien; Novia Trisnasari; Nurul Kamariyah; Rusdianingseh (Universitas STRADA Indonesia, 2025)
Background: Pulmonary Tuberculosis is one of the top ten causes of death worldwide. Case detection rate in East Java ranks eighth in Indonesia, namely 42.922 cases with treatment coverage of 44.7% of the treatment coverage target set at a minimum of 80%. Factors related to success include knowledge, attitudes, beliefs, work, etc. One of the supporting factors related to the success of treatment is the role of the drug swallowing supervisor. Purpose: The purpose of this study was to determine the relationship between the role of drug swallowing supervisor in the treatment of patients with pulmonary tuberculosis. Methods: The research design uses correlational, population analytic methods. Respondents used are 41 out of 46 pulmonary tuberculosis sufferers at health center in Surabaya using simple random sampling technique. The independent variable of the study is the role of drug swallowing supervisor and the dependent is the success of the treatment. The instrument use questionnaire and medical records. Results: Data processed using chi square test analysis, value = 0.05. The results showed that almost all of the 41 respondents (87.8%) had supportive drug swallowing supervisor, almost all (78%) the treatment was successful. Based on statistical tests obtained (p = 0.000) which proves that the role of drug swallowing supervisor has a relationship with the success of treatment in patients with pulmonary tuberculosis. Conclusion: The greater the supporting role, the greater the success rate of pulmonary tuberculosis treatment. It is expected that drug swallowing supervisor can motivate, assist, remind, and participate in socialization activities for handling pulmonary tuberculosis patients.